Echinococcus granulosus: Ultrastructural Effect of Albendazole Therapy - Magamboa, J. K.; Zeyhle, E.; Nganda, N. T.; Raasen, T.; Wachira, J. (African Journal of Health Sciences, 1994)
The effects of the anthelmintic Albendazole against Echinococcus granulosus hydatid cysts in Turkana patients given orally were studied by means of ultrasound as well as light microscopy, scanning and transmission electron microscopy. The treatment generally reduced the size of the cyst mass, making the patients feel well. The drug therapy caused collapse of the cyst wall and daughter cyst. The pathological changes on the germinal layer of Albendazole-treatment cysts differed widely from the untreated control hydatid tissue. The effects included morphological changes of the protoscolices, presence of lamellated bodies, necrosis with detachment of the germinal layer from the laminated layer. However, some parts of the Albendazole-treated hydatid tissue remained unaffected.
Abstract
Keywords: Anthelmintic Albendazole; Hydatid cysts; Turkana